A predictive framework for the reproducible seed-mediated synthesis and functionalization of gold nanorods - Brian Novati; Lucia Salvioni; Melissa Saibene; Alessandro Colombo; Roberto Lorenzi; Angelo Monguzzi; Stefania Garbujo; Miriam Colombo; Marco D. Giustra; Davide Prosperi (Chemical Engineering Journal, 2026)

Exploring overlooked non-extractable phenolics in pecan nut residues through an LC–MS-based approach - Thanise Antunes Dias; Mateus Colombo; Alessandro de Oliveira Rios; Simone Hickmann Flôres; Eliseu Rodrigues (Food Chemistry, 2026)

Climber’s muscle excitation and force distribution at different wall angles and body positions - Eleonora Bonelli; Susanna Rampichini; Fabio Esposito; Giulio Rossi; Alessandro Colombo; Eloisa Limonta (European Journal of Applied Physiology, 2026)
Purpose In the domain of rock climbing research, existing biomechanical and physiological studies mostly focus on few, typically upper-body muscles and frequently do not replicate ecological conditions. This study investigates full-body muscle excitation and contact forces between climber and holds in two stationary climbing stances. Methods Surface electromyography of 22 upper and lower-body muscles and contact forces between climber and holds were recorded in 14 climbers (6 males, 8 females; age 24 ± 6 years; height 1.71 ± 0.07 m; mass 64 ± 8 kg; IRCRA 11–23). We recorded contact forces at three vertices of a rectangle: feet on the lower vertices, right hand on the upper right vertex. The protocol involved five repetitions of two 10-s positions (UP and DOWN) at three wall angles (SLAB: + 5°; VERTICAL: 0°; OVERHANG: −5). Root-mean-square values of electromyographic signals were determined for each repetition and scenario. A two-way RM-ANOVA assessed differences by wall angle and position. Results and conclusion Steeper wall angles cause load transfer from feet to hand, homolateral in UP and contralateral in DOWN. DOWN position involves greater excitation of finger flexors muscles and brachioradialis at all wall angles, suggesting that preference for DOWN position in OVERHANG may not be simply explained by the degree of excitation of those muscles. This study provides a comprehensive mapping of full-body superficial muscle excitation and contact forces across two ecological climbing positions at different wall angles, helping to clarify climbing kinetics, inform targeted training and rehabilitation exercises, and optimize protocols for future research.

Developing 3D vitrification for cat oocytes: Viability, maturation and actin pattern - Martina Colombo; Alessandra Mascaro; Jasmine Fusi; Alessandro Pecile; Gaia Cecilia Luvoni (Cryobiology, 2025)

Dynamic emission inventory of ammonia in northern Italy by machine learning - Alessandro Marongiu; Loris Colombo; Anna Gilia Collalto (Air Quality, Atmosphere & Health, 2025)

Antioxidant and antiapoptotic effect of melatonin on cat vitrified oocytes - Martina Colombo; Alessandra Mascaro; Alessandro Pecile; Jasmine Fusi; Gaia Cecilia Luvoni (Theriogenology, 2025)

Toxicity of real-world PM2.5 road tunnel emissions using a mobile air-liquid interface system and submerged exposure - Micol Introna; Ana Teresa Juárez-Facio; Naga Veera Srikanth Vallabani; Ming Hui Tu; Paavo Heikkilä; Andrea Colombo; Valentina Liboni; Bozhena Tsyupa; Alessandro Mancini; Jorma Keskinen; Ulf Olofsson; Sarah Sulamith Steimer; et al. (Environmental Pollution, 2025)

Immunization thresholds to change the overall level and the effect of cases on deaths by COVID-19 in pregnant and postpartum women - Alessandro José Queiroz Sarnaglia; Luciana Graziela de Godoi; Nátaly Adriana Jiménez Monroy; Fabio Alexander Fajardo Molinares; Bartolomeu Zamprogno; Diego Roberto Colombo Dias; Agatha Sacramento Rodrigues (Environmental Research, 2025)

Modelling of spacecraft apparent brightness A study on OneWeb constellation satellites - Gerardo Littoriano; Camilla Colombo; Alessandro Nastasi; Carmelo Falco (Advances in Space Research, 2024)

PM2.5 wintertime sensitivity to changes in NOx, SO2, and NH3 emissions in Lombardy Region - Loris Colombo; Alessandro Marongiu; Giuseppe Fossati; Giulia Malvestiti; Elisabetta Angelino (Air Quality, Atmosphere & Health, 2024)

Generation of fused visible and thermal-infrared images for uncooperative spacecraft proximity navigation - Gaia Letizia Civardi; Michele Bechini; Matteo Quirino; Alessandro Colombo; Margherita Piccinin; Michèle Lavagna (Advances in Space Research, 2024)

Reappraisal of red clays in porcelain stoneware production: Compositional and technological characterization - Riccardo Fantini; Sonia Conte; Alessandro F. Gualtieri; Michele Dondi; Francesco Colombo; Mattia Sisti; Chiara Molinari; Chiara Zanelli; Rossella Arletti (Applied Clay Science, 2024)

Exposure to secondhand and thirdhand smoke in private vehicles: Measurements in air and dust samples - Xavier Continente; Elisabet Henderson; Laura López-González; Esteve Fernández; Olena Tigova; Sean Semple; Rachel O'Donnell; Ana Navas-Acién; Núria Cortés-Francisco; Noelia Ramírez; Ruaraidh Dobson; Maria José López; et al. (Environmental Research, 2023)

Empirical insights on the use of sun-induced chlorophyll fluorescence to estimate short-term changes in crop transpiration under controlled water limitation - Kazi Rifat Ahmed; Eugenie Paul-Limoges; Uwe Rascher; Jan Hanus; Franco Miglietta; Roberto Colombo; Alessandro Peressotti; Andrea Genangeli; Alexander Damm (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Global Proteomic Profile Integrated to Quantitative and Morphometric Assessment of Enteric Neurons: Investigation of the Mechanisms Involved in the Toxicity Induced by Acute Fluoride Exposure in the Duodenum - Carina Guimaraes de Souza Melo; Jacqueline Nelisis Zanoni; Sara Raquel Garcia de Souza; Isabela Zignani; Aline de Lima Leite; Alessandro Domingues Heubel; Juliana Vanessa Colombo Martins Perles; Marília Afonso Rabelo Buzalaf (Neurotoxicity Research, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Litter fractions and dynamics in a degraded pine forest after thinning treatments - Alessandra Lagomarsino; Gianluigi Mazza; Alessandro Elio Agnelli; Romina Lorenzetti; Caterina Bartoli; Carlo Viti; Claudio Colombo; Roberta Pastorelli (European Journal of Forest Research, 2020)

Correction to: Psychiatric disorders and SLC6A4 gene variants: possible effects on alcohol dependence and alzheimer’s disease - Marco Calabrò; Laura Mandelli; Concetta Crisafulli; Stefano Porcelli; Diego Albani; Antonis Politis; George N. Papadimitriou; Marco Di Nicola; Luigi Janiri; Roberto Colombo; Giovanni Martinotti; Antonello Bellomo; et al. (Molecular Biology Reports, 2020)

Psychiatric disorders and SLC6A4 gene variants: possible effects on alcohol dependence and alzheimer’s disease - Marco Calabrò; Laura Mandelli; Concetta Crisafulli; Stefano Porcelli; Diego Albani; Antonis Politis; George N. Papadimitriou; Marco Di Nicola; Luigi Janiri; Roberto Colombo; Giovanni Martinotti; Antonello Bellomo; et al. (Molecular Biology Reports, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The calcium-binding type III repeats domain of thrombospondin-2 binds to fibroblast growth factor 2 (FGF2) - Marco Rusnati; Patrizia Borsotti; Elisabetta Moroni; Chiara Foglieni; Paola Chiodelli; Laura Carminati; Denise Pinessi; Douglas S. Annis; Giulia Paiardi; Antonella Bugatti; Alessandro Gori; Renato Longhi; et al. (Angiogenesis, 2019)

White Matter Microstructure in Bipolar Disorder Is Influenced by the Interaction between a Glutamate Transporter EAAT1 Gene Variant and Early Stress - Sara Poletti; Irene Bollettini; Cristina Lorenzi; Alice Vitali; Silvia Brioschi; Alessandro Serretti; Cristina Colombo; Francesco Benedetti (Molecular Neurobiology, 2019)

A Glutamate Transporter EAAT1 Gene Variant Influences Amygdala Functional Connectivity in Bipolar Disorder - Sara Poletti; Martina Riberto; Benedetta Vai; Davide Ghiglino; Cristina Lorenzi; Alice Vitali; Silvia Brioschi; Clara Locatelli; Alessandro Serretti; Cristina Colombo; Francesco Benedetti (Journal of Molecular Neuroscience, 2018)

Suppressing effect of COR659 on alcohol, sucrose, and chocolate self-administration in rats: involvement of the GABAB and cannabinoid CB1 receptors - Paola Maccioni; Giancarlo Colombo; Irene Lorrai; Alessandro Zaru; Mauro A. M. Carai; Gian Luigi Gessa; Antonella Brizzi; Claudia Mugnaini; Federico Corelli (Psychopharmacology, 2017)

Elevated reinforcing and motivational properties of alcohol at the end of the nocturnal period in sP rats - Paola Maccioni; Irene Lorrai; Maria Francesca Marras; Andrea Contini; Alessandro Capra; Gessica Piras; Pierluigi Caboni; Gian Luigi Gessa; Giancarlo Colombo (Psychopharmacology, 2015)

Immunomodulatory Effects of a Low-Dose Clarithromycin-Based Macrolide Solution Pressurised Metered Dose Inhaler - Mehra Haghi; Alessandro Saadat; Bing Zhu; Gaia Colombo; Gregory King; Paul M. Young; Daniela Traini (Pharmaceutical Research, 2015)

The Cannabinoid CB1 Receptor Antagonist, Rimonabant, as a Promising Pharmacotherapy for Alcohol Dependence: Preclinical Evidence - Giancarlo Colombo; Alessandro Orrù; Paola Lai; Claudia Cabras; Paola Maccioni; Marina Rubio; Gian Luigi Gessa; Mauro A. M. Carai (Molecular Neurobiology, 2007)

Reducing effect of the positive allosteric modulator of the GABAB receptor, GS39783, on alcohol self-administration in alcohol-preferring rats - Paola Maccioni; Daniela Pes; Alessandro Orrù; Wolfgang Froestl; Gian Luigi Gessa; Mauro A. M. Carai; Giancarlo Colombo (Psychopharmacology, 2007)

Lack of tolerance to the suppressing effect of rimonabant on chocolate intake in rats - Gian Luigi Gessa; Alessandro Orrù; Paola Lai; Paola Maccioni; Rossella Lecca; Carla Lobina; Mauro A. M. Carai; Giancarlo Colombo (Psychopharmacology, 2006)

The effect of residual water on antacid properties of sucralfate gel dried by microwaves - Alessandro Gainotti; Elena Losi; Paolo Colombo; Patrizia Santi; Fabio Sonvico; Daniela Baroni; Gina Massimo; Gaia Colombo; Pasquale Del Gaudio (AAPS PharmSciTech, 2006)